Audit Delay Analysis: The Influence Of Financial Distress, Leverage, And Management Change - Wijaya, Natasya; Prastiwi, Dewi (International Economic Conference of Business and Accounting, 2024)
Audit Delay is the time interval for completion of the audit measured from the closing date of the financial year, until the opinion of the financial statements audited by the independent auditor has been signed. In Indonesia, there are still many companies that are late in reporting financial reports on time. The Financial Services Authority (OJK) stipulates that financial reports must be published immediately a maximum of 90 days from the end of the fiscal year. The audit delay phenomenon could be due to a lack of relevance in the financial statements presented to investors. This study aims to determine how much financial distress, leverage, and management changes can affect audit delay in all manufacturing companies listed on the Indonesia stock exchange in 2019-2021 both partially and simultaneously. The approach used in this research is a quantitative approach. The sample selection in this study used the exhibitive sampling method, and obtained 18 companies for 3 years (2019-2021), so that the total sample was 54 samples. The data analysis technique in this study used linear regression analysis. The results of this study indicate that the financial grieving variable has a negative effect on audit delay, while the capital and management variables have no effect on audit delay.